The Grog mob: Lessons from an evaluation of a multi-disciplinary alcohol intervention for Aboriginal clients - D'Abbs, P.; Togni, S.; Rosewarne, C.; Boffa, John (2013)
Objectives: To evaluate a 12-month trial of an evidence-based non-residential treatment program for Indigenous clients with alcohol problems, offering three streams of care: pharmacotherapy, psychological and social support. Methods: Process evaluation of program implementation; outcome evaluation of client outcomes. Results: Implementation: despite constraints of time and remoteness, the trial demonstrated the feasibility of implementing such a program. The medical stream generated fewer pharmacotherapy prescriptions than expected. The most active stream was the psychological therapy stream. Outcomes: between March 2008 and April 2009, 129 clients were referred to the program, of whom 49 consented to have de-identified data used for the evaluation. Of these, 19 clients received one or more streams of care, 15 of whom (78.9%) subsequently stopped or reduced drinking. However, among the remaining 30 consenting clients who had not received an intervention, 70.0% also reported stopping or reducing drinking. The evidence of program effectiveness is therefore equivocal and evaluation over a longer period is required. Conclusion and implications: The trial demonstrated the viability of, and demand for, evidence-based non-residential treatment for Indigenous clients with alcohol problems. Reasons behind an apparent reluctance among GPs to prescribe pharmacotherapy for Indigenous clients, and steps to overcome this, need further attention. © 2013 The Authors. ANZJPH © 2013 Public Health Association of Australia.